Efficacy and Safety of Trametinib Monotherapy or in Combination With Dabrafenib in Pediatric BRAF V600–Mutant Low-Grade Glioma. Issue 3 (14th November 2022) - Bouffet, Eric; Geoerger, Birgit; Moertel, Christopher; Whitlock, James A.; Aerts, Isabelle; Hargrave, Darren; Osterloh, Lisa; Tan, Eugene; Choi, Jeea; Russo, Mark; Fox, Elizabeth
Abstract : PURPOSE: BRAF V600 mutations occur in many childhood cancers, including approximately 20% of low-grade gliomas (LGGs). Here, we describe a phase I/II study establishing pediatric dosing and pharmacokinetics of trametinib with or without dabrafenib, as well as efficacy and safety in a disease-specific cohort with BRAF V600–mutant LGG; other cohorts will be reported elsewhere. METHODS: This is a four-part, phase I/II study (ClinicalTrials.gov identifier: NCT02124772 ) in patients age < 18 years with relapsed/refractory malignancies: trametinib monotherapy dose finding (part A) and disease-specific expansion (part B), and dabrafenib + trametinib dose finding (part C) and disease-specific expansion (part D). The primary objective assessed in all patients in parts A and C was to determine pediatric dosing on the basis of steady-state pharmacokinetics. Disease-specific efficacy and safety (across parts A-D) were secondary objectives. RESULTS: Overall, 139 patients received trametinib (n = 91) or dabrafenib + trametinib (n = 48). Trametinib dose-limiting toxicities in > 1 patient (part A) included mucosal inflammation (n = 3) and hyponatremia (n = 2). There were no dose-limiting toxicities with combination therapy (part C). The recommended phase II dose of trametinib, with or without dabrafenib, was 0.032 mg/kg once daily for patients age < 6 years and 0.025 mg/kg once daily for patients age ≥ 6 years; dabrafenib dosing in the combination was as previously identified for monotherapy. In 49 patients with BRAF V600–mutant glioma (LGG, n = 47) across all four study parts, independently assessed objective response rates were 15% (95% CI, 1.9 to 45.4) for monotherapy (n = 13) and 25% (95% CI, 12.1 to 42.2) for combination (n = 36). Adverse event–related treatment discontinuations were more common with monotherapy (54% v 22%). CONCLUSION: The trial design provided efficient evaluation of pediatric dosing, safety, and efficacy of single-agent and combination targeted therapy. Age-based and weight-based dosing of trametinib with or without dabrafenib achieved target concentrations with manageable safety and demonstrated clinical efficacy and tolerability in BRAF V600–mutant LGG.